1994
DOI: 10.1128/jcm.32.9.2046-2049.1994
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two commercial human T-cell lymphotropic virus western blot (immunoblot) kits with problem specimens

Abstract: We evaluated two commercial human T-cell lymphotropic virus (HTLV) Western blot (WB; immunoblot) kits, Cambridge Biotech Corp. (CBC) and Diagnostic Biotechnology Ltd. (DBL). Both methods employ HTLV type I (HTLV-I) viral lysate and rgp2l. The DBL WB kit also distinguishes between HTLV-I and HTLV-II antibodies, using an HTLV-I-specific and an HTLV-II-specific recombinant. Fifty weakly reactive HTLV-IIpositive plasma specimens which were falsely negative with the Abbott enzyme immunoassay (EIA) and 50 Ortho EIA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 6 publications
0
3
0
2
Order By: Relevance
“…Our group has further demonstrated that the lack of reactivity to rgp46 2 in specimens from Seminole Indians was not due to sequence variation but, rather, reflected lower titers of HTLV-2 antibodies (15). A larger study with HTLV enzyme immunoassay-negative specimens (PCR positive for HTLV-2) has further revealed that specimens containing low titers of antibodies to HTLV-1/2 also can be missed by this test (5). We therefore strongly recommend that all diagnostic specimens with reactivity to p24 and GD21-I continue to be referred to as HTLV-positive untypeable, requiring further testing by more sensitive assays.…”
Section: Discussionmentioning
confidence: 69%
“…Our group has further demonstrated that the lack of reactivity to rgp46 2 in specimens from Seminole Indians was not due to sequence variation but, rather, reflected lower titers of HTLV-2 antibodies (15). A larger study with HTLV enzyme immunoassay-negative specimens (PCR positive for HTLV-2) has further revealed that specimens containing low titers of antibodies to HTLV-1/2 also can be missed by this test (5). We therefore strongly recommend that all diagnostic specimens with reactivity to p24 and GD21-I continue to be referred to as HTLV-positive untypeable, requiring further testing by more sensitive assays.…”
Section: Discussionmentioning
confidence: 69%
“…Before each MPEP shipment, all donor samples were tested independently by two laboratories to confirm retroviral serologic status by using all available HTLV and HIV EIA test kits licensed by the FDA and all available WB kits. In addition, each HTLV‐I/II antibody‐positive donor sample was tested by RIPA and, since 1994, by type‐specific WB and indirect immunofluorescent (IIF) antibody assays capable of distinguishing HTLV‐I from HTLV‐II 3,4 . Preshipment HTLV‐positive serologic status of donor samples was based on repeatedly reactive results on all FDA‐licensed HTLV EIAs and demonstration of antibody to both core and envelope antigens in HTLV WBs and/or RIPA 1 .…”
Section: Methodsmentioning
confidence: 99%
“…This would have increased the specificity of the HTLV WB 2.4 kit to 86%. They concluded that the indeterminated WB are caused by lack of sensitivity and specificity of the WB antigen and poor interpretation criteria, not by variances of the specimens [Gallo et al 1994].…”
Section: Discussionmentioning
confidence: 99%
“…É possível considerar que o sistema imune é um fator importante e podem resultar as amostras de soro em indeterminado, possivelmente pela menor produção de anticorpos anti-HTLV-2(Bassini et al, 2006). No entanto, nossos resultados indicam que a contagem células T não influenciou na presença dos resultados indeterminados, mesmo em indivíduos infectados pelo HIV-1 Gallo et al (1994). constataram que o teste de WB tinha uma sensibilidade de 68%, com fracas bandas nos resultados de HTLV-2 positivos e uma especificidade de 70% com os negativos.…”
unclassified
See 1 more Smart Citation